Sensory quality of milk fat with low cholesterol content fractioned by molecular distillation - Berti, Julia (2018)
Anhydrous milk fat (AMF) is a valuable ingredient in several industries, but its cholesterol content is a disadvantage because it is associated with several diseases. The objective of this study was to remove the largest possible amount of cholesterol from AMF by molecular distillation and to analyze the sensory properties of the obtained product. AMF was subjected to various molecular distillation arrangements. RESULTS: The first set of experiments involved molecular distillations performed over a range of evaporation temperatures. Then, according to the outcome of the first set of experiments, a second set of experiments was carried out in order to study the effect of the feeding flow rate. Finally, the number of distillation stages was modified. The best results were obtained in a three-stage arrangement, in which ∼60% of cholesterol was removed with a 30.48% distillate yield. The sensory properties of this distillation cut were also the most similar to those of the untreated milk fat.